From Design for One to Open-ended Design. Experiments on understanding how to open-up contextual design solutions. (28th July 2017) - Ostuzzi, Francesca; De Couvreur, Lieven; Detand, Jan; Saldien, Jelle
Abstract: Online platforms (i.e. Instructables) often provide design solutions developed locally for one specific person's needs. The goal of the research is to understand how existing specific projects, created to be for one person, can be translated into open design solutions that facilitate spontaneous re-appropriation in a variety of new contexts. By observing and interviewing 36 teams of students within a living lab project where occupational therapists and designers co-design personal assistive devices with and for disabled clients, we explored how the relevant design information can be meaningfully reorganized to create open design . We focused on the designers' choices of concrete attributes with a high impact on the end-result. We suggest a model wherein these attributes are listed and categorized as: Undefined, Defined-Fixed, Contextual, balancing openness and over-design. The research led to a new definition that distinguishes "Open-ended Design" from "Open Design".